PREVALENCE AND DETERMINANTS OF MEDICATION NON-ADHERENCE IN BRONCHIAL ASTHMA: A CROSS-SECTIONAL STUDY FROM A TERTIARY CARE CENTER (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Medication adherence is a key determinant of asthma control; however, non-adherence remains a significant barrier to achieving optimal outcomes in bronchial asthma. Objective: To determine the prevalence of medication non-adherence, identify associated factors, and compare adherence between different inhaler devices among patients with bronchial asthma. Methods: A hospital-based cross-sectional study was conducted among 111 adult patients with bronchial asthma attending a tertiary care center. Data were collected using a structured questionnaire assessing demographic characteristics, clinical profile, inhaler device use, and adherence behavior. Adherence was evaluated using a self-reported method. Statistical analysis was performed using SPSS software, and associations were assessed using Chi-square or Fisher’s exact test. Results: The prevalence of medication non-adherence was 18.9%. Non-adherence was relatively higher among patients aged 21–40 years, females, and those residing in rural areas; however, these associations were not statistically significant. A marginally higher proportion of non-adherence was observed among dry powder inhaler users compared to metered-dose inhaler users. The most frequently reported reasons for non-adherence were perceived improvement in symptoms and lack of perceived need for continued therapy. Other contributing factors included fear of dependence, concerns regarding side effects, and difficulties related to inhaler use. Conclusion: Medication non-adherence affects a considerable proportion of patients with bronchial asthma and is predominantly driven by behavioral factors. Strengthening patient education and reinforcing adherence during follow-up are essential to improve disease control and outcomes.